Effect of wheat seed treatment with chemical elicitors on aphid-plant interaction - Glinwood, Robert (Swedish University of Agricultural Sciences, 2025)
The data contains counts of number of bird cherry-oat aphids (Rhopalosiphum padi) that settle on wheat (Triticum aestivum) plants after seed treatment with chemical elicitors and control plants (treated with water/wetter), and measures of the size of aphid populations on plants after treatment. Data were collected in glasshouse/growth chambers. Data were collected as part of the Swedish Research Council Formas project 2018-00706 to assess the potential of chemical elicitors methyl salicylate, methyl jasmonate and cis-jasmone for improving plant a health.

Aphid plant colonization: Ten aphids (Rhopalosiphum padi) were placed onto wheat plants (treated with elicitors or water control) at 2-leaf stage and the number of aphids settled on the plants after 2 hours was recorded.

Aphid population development: One adult aphid (Rhopalosiphum padi) was placed onto wheat plants (treated with elicitors or water control) and after it had produced nymphs, all but one nymph were removed. The number of days for each nymph to become adult and produce a first nymph (d) was recorded and the number of nymphs produced in a time equal to d (M) was recorded. The intrinsic rate of aphid population increase (Rm) was calculated using the formula Rm=0.74(LnM)/d

Aphid population development- Variable List:
Treatment (Control, MeSa= methyl salicylate, MeJa= methyl jasmonate, CJ= cis-jasmone), Concentration (concentration of elicitor mM (millimolar)), days to repr (d)= number of days between aphid birth and first reproduction no. offspring (M)= number of aphid offspring produced in time equivalent to d, no. offsring/day= M/d, Rm intrinsic rate of population increase calculated by Rm=0.74(LnM)/d. Experiment code A= MeSa vs control, B= MeJa vs control, C= CJ vs control.

This data file consists of 171 rows and 7 columns

Aphid plant colonization- Variable List:
Treatment (Control, MeSa= methyl salicylate, MeJa= methyl jasmonate, CJ= cis-jasmone), Conc (concentration of elicitor mM millimolar), no. aphids settled after 2 hrs, Experiment code (indicates which control treatment to compare with which elicitor treatment)

This data file consists of 240 rows and 5 columns. Identical values may appear on more than one row, so a unique data value identifier is included in the first column (Data point ID)

Data innehåller räkningar av antalet bladlöss (Rhopalosiphum padi) som koloniserar veteplantor (Triticum aestivum) efter fröbehandling med kemiska substanser samt på kontrollväxter (behandlade med vatten/vätare), och mått på storleken på bladluspopulationer på växter efter behandling. Data samlades in i växthus/tillväxtkammare. Se engelsk beskrivning för mer information.
Växt-bladlöss interaktioner efter behandling av vetefröer med kemiska elicitorer
Keywords: wheat; Aphids; bladlöss; Triticum aestivum; vete; Rhopalosiphum padi; triticum aestivum l.; rhopalosiphum padi (linnaeus, 1758); wheat; vete; aphid; bladlöss; bird cherry-oat aphid; havrebladlus; elicitor; elicitor; Zoology; Zoologi; Ecology; Ekologi; Agricultural Science; Jordbruksvetenskap